Analisis Kandungan Hasil Proses Gasifikasi Sekam Padi - Sanusi, Arifin; Jasron, Jahirwan Ut; Tamonob, Kristoforus (Universitas Nusa Cendana, 2022)
Rice husk biomass can be converted into renewable energy. Energy can be obtained by burning biomass directly, pyrolysis (without oxygen), or gasification (with limited oxygen) to produce liquid or gas fuel. Gasification is burning solid fuel in a gasifier container to produce gaseous fuel (syngas). This research was conducted by varying the mass of rice husk fuel to the gas produced by gasification. This study aimed to determine the effect of the mass of rice husk fuel on gas from gasification and the effect of gas from gasification of rice husk combustion on thermal efficiency. The results of the combustion of the gasification furnace show that the more rice husk mass, the more gas will be produced. Based on the thermal efficiency calculation results, a mass of 5 kg rice husk becomes 302.69%, and a mass of 10 kg rice husk becomes 250.75%, while a mass of 15 kg rice husk becomes 129.38%.